French costumes, 1685-1690 - Leloir, Maurice, 1853-1940:::Creator::: (H. Ernst)
Complete gentleman's dress made of silk brocade with silver ribbons. Dress of a lady of quality made of brocaded silk trimmed with silver lace with headress. French costumes from 1685-1690, drawn by Maurice Leloir.